The effectiveness of web-based training for parents on post-traumatic stress disorder in children - Omidvar Eshkalak, Zakieh; Parvizy, Soroor; Seyedfatemi, Naima; Haghani, Hamid; Nazari, Hadis (Frontiers in Psychology, 2024)
Introduction: Post-traumatic stress disorder (PTSD) after an injury such as accidents is common in children and can affect their overall physical and mental functioning and quality of life. Early intervention can have significant health benefits for children. This study aimed to investigate the effectiveness of web-based training for parents on post-traumatic stress disorder in children. Method: This was a quasi-experimental study with intervention and control group. 110 parents of children aged 10-18 years with PTSD after a traumatic event were selected through available sampling and assigned to experimental and control groups. Data was collected by a researcher-made demographic questionnaire and the Child Revised Impact of Events Scale (CRIES-8). Parents in the experimental group received a 4-week training course through a researcher-designed website, but the control group received routine care by the clinical team, which the main focus of care and training was on the physical aspects of the disease, and no intervention was done for PTSD. Two weeks after the intervention, the level of child stress was measured and compared in both groups. Data were analyzed using SPSS V.22. Results: The difference between the mean score of total traumatic stress and its subscales before intervention was not statistically significant (P=0.23). But after intervention, the mean score of total traumatic stress and its subscales decreased in the experimental group and increased in the control group and this difference was statistically significant (P<0.001). Conclusion: E-learning parent training has the potential to support children with PTSD. This available and cost-effective procedure can be recommended to help children with PTSD and possibly increase recovery in these patients.